Prostate Cancer and Aspirin Use: Synopsis of the Proposed Molecular Mechanisms - Bilani, Nadeem; Bahmad, Hisham; Abou-Kheir, Wassim (Frontiers in Pharmacology, 2017)
Background: Prostate cancer (PCa) is a critical health burden, impacting the morbidity and mortality of millions of men around the world. Most of the patients with PCa have their disease at first sensitive to androgen deprivation treatments, but later they develop resistance to therapy and eventually die of metastatic castration-resistant prostate cancer (CRPC). Although the newly developed anti-androgen therapies are effectively alleviating symptoms and prolonging lives of patients, there are still no curable treatments for CRPC. Recently, statistical studies have shown that the chronic use of aspirin might be significantly associated with better outcomes in PCa patients. Through this review, we aim to identify the different proposed molecular mechanisms relating aspirin to the pathobiology of PCa neoplasms, with a major focus on basic research done in this context. Methods: Articles were retrieved via online database searching of PubMed and MEDLINE between 1946 and September 2016. Keywords and combinations related to PCa and aspirin were used to perform the search. Abstracts of the articles were studied by two independent reviewers and then data extraction was performed on the relevant articles that met our review objectives. Results: Aspirin, a non-steroidal anti-inflammatory drug (NSAID), affects the proliferation, apoptosis, resistance and metastasis of PCa cell lines, through both COX-dependent and COX-independent mechanisms. It also lowers levels of the PCa diagnostic marker prostate specific antigen (PSA), suggesting that clinicians need to at least be aware if their patients are using Aspirin chronically. Conclusion: This review strongly warrants further consideration of the signaling cascades activated by aspirin, which may lead to new knowledge that might be applied to improve diagnosis, prognosis and treatment of PCa.